Avaliação da relação entre os módulos de elasticidade estático e dinâmico de concretos produzidos com agregados graúdos reciclados em substituição aos agregados graúdos naturais - Sousa, Fernando Henrique Fernandes (Universidade do Vale do Rio dos Sinos, 2018)
Modulus of elasticity is a parameter that measures the stiffness of the concrete, being one of the properties taken into account in the structural safety check, since it expresses the conditions of the ultimate and service boundary state. When the influence of the replacement of natural aggregates by recycled aggregates is evaluated, the elastic behavior of the concrete becomes essential, since it cannot be compared to the behavior of compressive strength, usually lower than the concrete produced with natural aggregates. The use of compressive strength as a single parameter to estimate the modulus of elasticity of concrete produced with recycled aggregates has been increasingly questionated. Considering the influence of the use of recycled aggregate on the modulus of elasticity of concrete, only a few studies have compared the values of static elastic modulus and dynamic modulus. This research aims to evaluate the relationship between the static elastic modulus and the dynamic elastic modulus of concrete produced with recycled aggregates in replacement of natural aggregates, in order to correlate the type of aggregate to the modulus of elasticity, verifying the relationship between the two procedure of determination of elasticity modulus. Aggregates made of recycled concrete and of ceramic bricks were used in a replacement rate of 30% to the natural aggregate. The concretes were produced in three experimental proportions (lower w/c ratio, intermediate w/c ratio and higher w/c ratio). The properties evaluated at 28 days are: bulk concrete mass; porosity; compressive strength; static and dynamic modulus of elasticity. The main conclusions are: the recycled aggregate decrease the modulus of elasticity, mainly the dynamic modulus; there are no relationship between the static and dynamic modulus of elasticity of concrete produced with recycled aggregates; the static modulus of concrete produced with recycled aggregates has a higher relationship to the compressive strength; the dynamic modulus of elasticity is higher related to the porosity of concrete produced with recycled aggregates; the moduli of elasticity estimated by algebraic equations present high variability.
Keywords: Módulo de elasticidade estático; Módulo de elasticidade dinâmico; Concreto; Agregado reciclado de concreto; Agregado reciclado de cerâmica vermelha; Static modulus of elasticity; Dynamic modulus of elasticity; Concrete; Recycled aggregate concrete; Recycled ceramic aggregate; ACCNPQ::Engenharias::Engenharia Civil